If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -19 = 7x + 11 Reorder the terms: -19 + 9x = 7x + 11 Reorder the terms: -19 + 9x = 11 + 7x Solving -19 + 9x = 11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -19 + 9x + -7x = 11 + 7x + -7x Combine like terms: 9x + -7x = 2x -19 + 2x = 11 + 7x + -7x Combine like terms: 7x + -7x = 0 -19 + 2x = 11 + 0 -19 + 2x = 11 Add '19' to each side of the equation. -19 + 19 + 2x = 11 + 19 Combine like terms: -19 + 19 = 0 0 + 2x = 11 + 19 2x = 11 + 19 Combine like terms: 11 + 19 = 30 2x = 30 Divide each side by '2'. x = 15 Simplifying x = 15
| 15x^3+25x^2-60x= | | 8t-11=5t+19 | | -2(18-3t)=7y+2y | | -(5y+2)-(-4y-8)=1 | | 4-x=-5 | | 2(x+30)= | | 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 | | 54=(17x+3)+(25x+9) | | 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 | | 4(x+1)=8 | | 2p-1=-4p-19 | | (2y-5)-8+y=5 | | 80=(x+9)+(6x-6) | | x^2-42xy-343y^2=0 | | 48=(14x+4)+(24x+2) |